ISOLASI DAN KARAKTERISTIK BAKTERI PADA TANAH TERCEMAR MINYAK BUMI DI KECAMATAN LIRIK SEBAGAI RANCANGAN HANDOUT PEMBELAJARAN BIOLOGI SMA - Citra Fajri; Irda Sayuti; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research was conducted to determine the characteristics of bacteria on petroleum contaminated soil in the Lirik sub-district as a design of biology learning handouts in senior high schools in January 2019. The results of the study were used to design learning handouts on biology subjects. This research was conducted in two stages, namely the field research stage and the design phase of the learning handout. This type of research is descriptive and carried out by examination in the laboratory. The sampling technique in this study was conducted using a purposive sampling method. The results showed that the characteristics of the bacteria found were white, cream and clear colony. The form of the colony was found to be irregular and round. The edge of the colony is found undulate, wavy, flat and jagged. The elevation of colonies found is flat and arises. The most dominant form of basil bacteria cells is found and other cells form coccus. Gram negative bacteria are the dominant bacteria found and other gram-positive bacteria. The growth of isolates at petroleum concentrations was 2% better with growth until the fifth day of exponents. Isolate 2 is the isolate that gets the highest growth compared to other isolates. The results of this study can be used as a design of biology learning handouts in high schools to enrich teaching materials on the concept of the role of bacteria in life.Key Words: Bacteria, Characteristics, Desaign Handout